Forest Industry of Russia Smart Innovations and Success Stories - Zykov, Sergey V.; Dayneko, Dennis V.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book focuses on crisis management in forest industry of Russia. It is about the present, and the future, with a short retrospective about the past of the forest industry in Russia. It includes forecasting too and description of some of the best practices of developed countries to be implemented in Russia to overcome the crisis. The main theme of the book is smart innovations and innovative activities introduced and also those which are required in the forest industry of Russia. The book considers the effectiveness of innovations and institutional changes in the forest industry, which are an important direction of innovation activities required all together with technological and economic breakthrough with ecological aspects in priority. The necessity to implement the modern innovation system in the forest industry based on institutional changes is substantiated and thoroughly explained with successful examples of ongoing and future up-to-date smart innovations. The development of the forest innovation system is suggested for sustainable forest industry management; the key components of which are technological, product, institutional, and ecological innovations, as well as, innovative entrepreneurship. Realization of the innovation system for technological and intellectual improvement requires good scientific and personnel provision, anticipation of markets and tendencies of development for some decades ahead. The implied advanced technologies in the forest industry also include IT-, nano-, and biotechnologies. The success stories of the leading Russian and international companies in the forest industry of Russia are studied attentively in the book. The book presents a profound methodical and theoretical substantiation for the further implementation of the smart innovations and of the successful experience of the industry leading companies.
Introduction: Russian Forests and Forest industry -- The Forest industry of Russia: problems and challenges -- Forest industry Innovations and leading Forest companies experience -- Innovations effectiveness and their evaluation -- Forest innovation system and its implementation -- Program of innovative changes in the Forest industry -- Conclusions.
Keywords: Industrial Management; Business; Management science; Forestry; Environmental engineering; Biotechnology; Bioremediation; Industrial Management; Business and Management; Forestry; Environmental Engineering/Biotechnology.; Forests and forestry -- Russia; Forest management -- Russia